2017
DOI: 10.1016/j.neuron.2017.05.036
|View full text |Cite
|
Sign up to set email alerts
|

Feature Integration Drives Probabilistic Behavior in the Drosophila Escape Response

Abstract: Animals rely on dedicated sensory circuits to extract and encode environmental features. How individual neurons integrate and translate these features into behavioral responses remains a major question. Here, we identify a visual projection neuron type that conveys predator approach information to the Drosophila giant fiber (GF) escape circuit. Genetic removal of this input during looming stimuli reveals that it encodes angular expansion velocity, whereas other input cell type(s) encode angular size. Motor pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
187
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(193 citation statements)
references
References 73 publications
6
187
0
Order By: Relevance
“…For instance, as a male approaches a stationary female during courtship, she would appear to be looming. LC4 and LC16 have previously been shown to respond to looming stimuli to generate escape responses [23,10,11]; here, we show that in the context of mating, males can also utilize these cell populations to drive distinct courtship behaviors. In contrast to previous studies that have focused on the role of female-generated movement in mediating male chase behaviors [6,7,8,9,12], our experiments indicate that visual cues play a much broader role in regulating spatial and temporal aspects of mating-related social interactions.…”
Section: Discussionmentioning
confidence: 49%
“…For instance, as a male approaches a stationary female during courtship, she would appear to be looming. LC4 and LC16 have previously been shown to respond to looming stimuli to generate escape responses [23,10,11]; here, we show that in the context of mating, males can also utilize these cell populations to drive distinct courtship behaviors. In contrast to previous studies that have focused on the role of female-generated movement in mediating male chase behaviors [6,7,8,9,12], our experiments indicate that visual cues play a much broader role in regulating spatial and temporal aspects of mating-related social interactions.…”
Section: Discussionmentioning
confidence: 49%
“…In the next phase of model development, we will start with some of the most robust innate behaviors, such as the escape response, in which fruit flies jump directly away from a looming threat (von Reyn et al 2017). A looming threat can be simulated by presenting a booming visual stimulus on the small field neurons in the unilateral medulla, while the initiation of the escape behavior can be represented by the activation of the giant fiber neurons (Tanouye and Wyman 1980).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we showed that P9 receives inputs from LCs that serve as feature detectors, arguing that P9 participates in a shallow pathway from visual detection to motor command. Direct connections between visual projection neurons and DNs are also seen in the Giant Fiber escape pathway (Klapoetke et al, 2017;von Reyn et al, 2017;Strausfeld and Bassemir, 1983) and in visually guided flight control (Strausfeld and Gronenberg, 1990;Suver et al, 2016), suggesting a common circuit motif to minimize response times when rapid action is required.…”
Section: The P9 Walking Program Provides Steering Control During Objementioning
confidence: 99%